Sejarah Kebangkitan Madrasah Sebagai Lembaga Pendidikan Islam - Fitri, Anisatul (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
Madrasah is a place or institution for the implementation of Islamic education that has a long history. The rise of madrasas is the beginning of the formation of formal Islamic educational institutions. Institutionally, since the classical period until now, we can see the development of Islamic education from various aspects, on the other hand, general institutions that have an Islamic style have developed into madrasas, including kuttab, mosques and other institutions. Topics surrounding madrasas have their own uniqueness and are very interesting to study as material for discussion, the beginning of formal institutionalization of Islam was marked by the rise of madrasas. Referring to the scientific side, this discussion about madrasas is interesting for us to study.